2018
DOI: 10.1097/meg.0000000000001026
|View full text |Cite
|
Sign up to set email alerts
|

Disruption of the gut-liver axis in the pathogenesis of acute-on-chronic liver failure

Abstract: Acute-on-chronic liver failure (ACLF) is characterized by organ failure mediated by acute decompensation of cirrhosis. Recent studies have highlighted the importance of the gut-liver axis (GLS) and its association with ACLF pathogenesis. In this review, we discuss the mechanisms related to the alteration of the GLA and their involvement in ACLF pathogenesis and suggest some possible therapeutic options that could modulate the GLA dysfunction. This knowledge may provide information useful for the design of ther… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
24
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(24 citation statements)
references
References 76 publications
0
24
0
Order By: Relevance
“…The outcomes of patients with HBV-ACLF can be significantly improved if interventions are timely and appropriately provided (Ott et al, 2017). Recently, many studies have demonstrated that HBV-ACLF development is closely associated with disorders in immune function, intestinal bacterial translocation (BT), gut dysbiosis and inflammation (Verbeke et al, 2011;Wang and Li, 2015;Preveden et al, 2017;Zhang et al, 2018). A previous study showed that stimulation by translocated bacteria or bacterial products (e.g., lipopolysaccharide, lipoteichoic acid, peptidoglycans, and bacterial DNA) can activate the innate immune system and modify the adaptive immune system, resulting in inflammation, liver cell apoptosis, and progression to liver failure (Sandler et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…The outcomes of patients with HBV-ACLF can be significantly improved if interventions are timely and appropriately provided (Ott et al, 2017). Recently, many studies have demonstrated that HBV-ACLF development is closely associated with disorders in immune function, intestinal bacterial translocation (BT), gut dysbiosis and inflammation (Verbeke et al, 2011;Wang and Li, 2015;Preveden et al, 2017;Zhang et al, 2018). A previous study showed that stimulation by translocated bacteria or bacterial products (e.g., lipopolysaccharide, lipoteichoic acid, peptidoglycans, and bacterial DNA) can activate the innate immune system and modify the adaptive immune system, resulting in inflammation, liver cell apoptosis, and progression to liver failure (Sandler et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Acute-on-chronic liver failure (ACLF) develops in cirrhotic patients following bacterial infection, gastrointestinal bleeding, alcohol intake, or worsening of the underlying liver disease [1,2]. ACLF has a high risk of short-term mortality associated with development of multiple organ failure (MOF) [3,4].…”
Section: Introductionmentioning
confidence: 99%
“…The availability of a predictive biomarker of ACLF would improve the prognosis of cirrhotic patients. Increased intestinal permeability in cirrhotic patients may increase the risk of bacterial translocation across the intestinal barrier and inflammation, both of which are involved in the pathophysiology of ACLF [1,2]. Endotoxin (Et), a lipopolysaccharide (LPS), includes a core domain and lipid A in the outer membrane of Gram-negative bacteria [5,6].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In fact, bacterial infection is an important precipitating factor of ACLF in one-third of ACLF, irrespective of the etiology of preexisting CLD [ 11 , 12 ]. And the occurrence of bacterial infection is usually thought to be caused by systemic translocation of microbes from gut-derived organisms, impaired hepatic clearance mechanisms, and an ability of circulating immune cells to combat infectious cues [ 11 , 13 ].…”
mentioning
confidence: 99%